The effect of the serotonin transporter polymorphism (5-HTTLPR) on amygdala function: A meta-Analysis - Murphy, SE; Godlewska, B; Cowen, P; Mannie, Z; Harmer, C; Norbury, R; Munafò, MR (2013)
The 5-HTTLPR polymorphism has been widely regarded as a potential genetic risk factor for affective disorders. Consistent with this, this polymorphism has been associated with altered amygdala responses at rest and in response to aversive stimuli. However, the strength of this association remains uncertain. We sought to synthesize existing data on the association between the 5-HTTLPR polymorphism and amygdala activation and ascertain the strength of evidence for this association. Meta-Analytic techniques were applied to data from relevant published studies and unpublished data sets to obtain an estimate of the likely magnitude of effect of any association. The large number of studies allowed us to apply a formal test of publication bias, as well as explore the impact of various study-level characteristics on the magnitude of the observed effect size. Our meta-Analysis indicated that there is a statistically significant but small effect of 5-HTTLPR on left and right amygdala activity. However, there was considerable between-study heterogeneity, which could not be fully accounted for by the study design and sample characteristics that we investigated. In addition, there was evidence of excess statistical significance among published studies. These findings indicate that the association between the 5-HTTLPR and amygdala activation is smaller than originally thought, and that the majority of previous studies have been considerably under powered to reliably demonstrate an effect of this size. © 2013 Macmillan Publishers Limited.